Scaling solution for field-dependent gauge couplings in quantum gravity - Wetterich, Christof (Arxiv, 2022)
Quantum gravity can determine the field-dependence of gauge couplings. This prediction is based on the scaling solution of functional flow equations. For momenta below the field-dependent Planck mass the quantum scale invariant standard model emerges as an effective low energy theory. For a small non-zero value of the infrared cutoff scale the fifth-force effects of time-varying couplings or apparent violations of the equivalence principle turn out to be negligibly small for the present cosmological epoch. More sizable effects of quantum scale symmetry violation are expected during nucleosynthesis or before. The scaling solution of metric quantum gravity yields restrictions for model building, as limiting the number of scalars in grand unified theories.
Version 1 vom 14 Mai 2022, Version 2 vom 2. August 2022
Gesehen am 26.10.2022